Non-tariff barriers: Ukrainian practice under conflict with Russia and COVID-19 - Коваль, Наталія Олексіївна; Коваль, Н. О.; Коваль, Наталья Алексеевна; Koval, Natalia O.; Лученко, Дмитро Валентинович; Лученко, Дмитрий Валентинович; Лученко, Д. В.; Luchenko, Dmytro V. (Publishing house Helvetica, 2020)
This article deals with the study of Ukraine’s measures of non-tariff barriers during the armed conflict in eastern Ukraine and under the conditions of the COVID-19 pandemic. The first part of the article identifies the reasons for the establishment and genesis of non-tariff barriers to foreign trade. The modern international legal basis of non-tariff regulation and its application in Ukraine is also outlined. Moreover, the impact of the EU-Ukraine Association Agreement 2014 on the mechanisms for setting non-tariff barriers is described. The second part of the article focuses on the characteristics of modern approaches to the classification of measures of non-tariff barriers to trade. Their diversity and lack of a definitive, orderly list in international agreements and national legislation are emphasized. The third part of the article is devoted to the analysis of measures of non-tariff barriers to trade, which were applied by Ukraine in relations with the Russian Federation and under the conditions of the COVID-19 pandemic. Their adequacy to the current crises in Ukraine was stated, but their untimeliness contributed to a significant reduction in efficiency in minimizing the negative impact of crises caused by the aggression of the Russian Federation and the COVID pandemic.

Ця стаття присвячена вивченню в Україні заходів щодо нетарифних бар’єрів під час збройного конфлікту на сході України та в умовах пандемії COVID-19. У першій частині статті визначено причини встановлення та генезису нетарифних бар'єрів для зовнішньої торгівлі. Також окреслено сучасну міжнародно-правову основу нетарифного регулювання та його застосування в Україні. Крім того, описано вплив Угоди про асоціацію між Україною та ЄС 2014 року на механізми встановлення нетарифних бар'єрів. Друга частина статті присвячена характеристикам сучасних підходів до класифікації заходів нетарифних бар’єрів у торгівлі. Підкреслюється їх різноманітність та відсутність чіткого, упорядкованого переліку в міжнародних угодах та національному законодавстві. Третя частина статті присвячена аналізу заходів нетарифних бар'єрів у торгівлі, які застосовувались Україною у відносинах з Російською Федерацією та в умовах пандемії COVID-19. Було заявлено про їх адекватність поточним кризам в Україні, але несвоєчасність сприяла значному зниженню ефективності мінімізації негативного впливу криз, спричинених агресією Російської Федерації та пандемією COVID.

Данная статья посвящена исследованию украинских мер нетарифных барьеров во время вооруженного конфликта на востоке Украины и в условиях пандемии COVID-19. В первой части статьи определены причины возникновения и генезиса нетарифных барьеров во внешней торговле. Также изложены современные международно-правовые основы нетарифного регулирования и их применение в Украине. Кроме того, описывается влияние Соглашения об ассоциации между ЕС и Украиной 2014 года на механизмы установления нетарифных барьеров. Вторая часть статьи посвящена характеристике современных подходов к классификации мер нетарифных барьеров в торговле. Подчеркивается их разнообразие и отсутствие окончательного и упорядоченного перечня в международных соглашениях и национальном законодательстве. Третья часть статьи посвящена анализу мер нетарифных барьеров в торговле, которые применялись Украиной в отношениях с Российской Федерацией и в условиях пандемии COVID-19. Была заявлена ​​их адекватность текущим кризисам в Украине, но их несвоевременность способствовала значительному снижению эффективности минимизации негативного воздействия кризисов, вызванных агрессией Российской Федерации и пандемией COVID.
Koval N. Non-tariff barriers: Ukrainian practice under conflict with Russia and COVID-19 / N. Koval, D. Luchenko // Lex Portus. – V. 4 (24). – Publishing house Helvetica, 2020. – P. 56–76.
Keywords: customs regulation; customs policy; trade policy; foreign economic activities; customs legislation; Ukraine; harmonization; COVID-19 pandemic; митне регулювання; митна політика; торгова політика; зовнішньоекономічна діяльність; митне законодавство; Україна; гармонізація; пандемія COVID-19; таможенное регулирование; таможенная политика; торговая политика; внешнеэкономическая деятельность; таможенное законодательство; Украина; гармонизация; пандемия COVID-19; Research Subject Categories::LAW/JURISPRUDENCE